Plasminogen Activator Inhibitor-1 mRNA Is Induced by Hemorrhage in Endothelial and/Mesothelial Cells of the Rat Liver - Yamashita, Masatomo; Darlington, Daniel N; Imafuku, Shiqichi; Gann, Dionald S (Thrombosis and Haemostasis, 1995)
We have recently shown that plasminogen activator inhibitor-1 (PAI-I) mRNA is elevated after hemorrhage in various tissues including liver. In this study, we set out to identify the cell types in the liver that are responsible for the increase in PAH mRNA after hemorrhage using in situ reverse transcription-polymerase chain reaction (in situ RT-PCR). Male Sprague-Dawley rats were cannulated and subjected to a 20 ml/kg hemorrhage within 3 min or 300 μg/kg of endotoxin. Pour hours later, the livers were harvested, fixed, frozen, and sectioned. RT-PCR showed an increase of PAI-I mRNA in liver 4 h after hemorrhage or endotoxin-treatment. Standard in situ hybridization could not detect PAI-I mRNA in the livers of either the hemorrhage, endotoxin, or control groups. However, in situ RT-PCR detected PAI-1 mRNA in vascular endothelial cells and capsular mesothelial cells, but not in hepatocytes, in both the hemorrhage and endotoxin groups. No signal was found in the control rats, or when the experimental protocol was modified to 1) omit the RT step, 2) precede the RT step with RNA digestion, or 3) use an irrelevant probe. These results demonstrate that hemorrhage induces PAI-1 mRNA in endothelial and mesothelial cells of liver.